PlexinD1 signaling controls domain-specific dendritic development in newborn neurons in the postnatal olfactory bulb - Sawada, Masato; Hamaguchi, Ayato; Mano, Naomichi; Yoshida, Yutaka; Uemura, Akiyoshi; Sawamoto, Kazunobu (Frontiers in Neuroscience, 2023)
Newborn neurons show immature bipolar morphology and continue to migrate toward their destinations. After the termination of migration, newborn neurons undergo spatially controlled dendrite formation and change into a complex morphology. The mechanisms of dendritic development of newborn neurons have not been fully understood. Here, we show that in the postnatal olfactory bulb (OB), the Sema3E-PlexinD1 signaling, which maintains bipolar morphology of newborn neurons, also regulates their dendritic development after the termination of migration in a dendritic domain-specific manner. Genetic ablation of Sema3E or PlexinD1 enhanced dendritic branching in the proximal domain of the apical dendrites of OB newborn granule cells, whereas PlexinD1 overexpression suppressed it in a Rho binding domain (RBD)-dependent manner. Furthermore, RhoJ, a small GTPase that directly binds to PlexinD1RBD in vascular endothelial cells, is expressed in migrating and differentiating newborn granule cells in the OB and is also involved in the suppression of proximal branching of their apical dendrites. These results suggest that the Sema3E-PlexinD1-RhoJ axis regulates domain-specific dendrite formation of newborn neurons in the postnatal OB.